Highly efficient phosphor-glass composites by pressureless sintering - Dao Zhang (Nature Portfolio, 2020)
Phosphor-glass/ceramic composites are attractive for high-power white light-emitting diodes, but interfacial reaction leads to loss of quantum efficiency. Here the authors report a reduction sintering method for embedment of phosphors into silica glass with limited interfacial reaction.